Dark I-Love-Q - Jing-Yi Wu; Wei Li; Xin-Han Huang; Kilar Zhang (European Physical Journal C: Particles and Fields)
Abstract For neutron stars, there exist universal relations insensitive to the equation of states, the so called I-Love-Q relations, which show the connections among the moment of inertia, tidal Love number and quadrupole moment. In this paper, we show that these relations also apply to dark stars, bosonic or fermionic. The relations can be extended to higher ranges of the variables, clarifying the deviations for dark stars in the literature, as those curves all approximate the ones generated by a polytropic equation of state, when taking the low density (pressure) limit. Besides, we find that for equation of states with scaling symmetries, the I-Love-Q curves do not change when adjusting the scaling parameters.